Graphene Oxide-Gold Nanosheets Containing Chitosan Scaffold Improves Ventricular Contractility and Function After Implantation into Infarcted Heart - Saravanan, Sekaran; Sareen, Niketa; Abu-El-Rub, Ejlal; Ashour, Hend; Sequiera, Glen Lester; Ammar, Hania I.; Gopinath, Venkatraman; Shamaa, Ashraf Ali; Sayed, Safinaz Salah Eldin; Moudgil, Meenal; Vadivelu, Jamuna; Dhingra, Sanjiv (Nature Research, 2018)
Abnormal conduction and improper electrical impulse propagation are common in heart after myocardial infarction (MI). The scar tissue is non-conductive therefore the electrical communication between adjacent cardiomyocytes is disrupted. In the current study, we synthesized and characterized a conductive biodegradable scaffold by incorporating graphene oxide gold nanosheets (GO-Au) into a clinically approved natural polymer chitosan (CS). Inclusion of GO-Au nanosheets in CS scaffold displayed two fold increase in electrical conductivity. The scaffold exhibited excellent porous architecture with desired swelling and controlled degradation properties. It also supported cell attachment and growth with no signs of discrete cytotoxicity. In a rat model of MI, in vivo as well as in isolated heart, the scaffold after 5 weeks of implantation showed a significant improvement in QRS interval which was associated with enhanced conduction velocity and contractility in the infarct zone by increasing connexin 43 levels. These results corroborate that implantation of novel conductive polymeric scaffold in the infarcted heart improved the cardiac contractility and restored ventricular function. Therefore, our approach may be useful in planning future strategies to construct clinically relevant conductive polymer patches for cardiac patients with conduction defects.